Grey sister - Lawrence, Mark, 1966- (Lawrence, Mark, 1966- Book of the Ancestor., 2019)
"Behind its walls, the Convent of Sweet Mercy has trained young girls to hone their skills for centuries. In Mystic Class, Novice Nona Grey has begun to learn the secrets of the universe. But so often even the deepest truths just make our choices harder. Before she leaves the convent, Nona must choose which order to dedicate herself to--and whether her path will lead to a life of prayer and service or one of the blade and the fist."--Back cover